Impact of Corporate Social Responsibility on Customer Trust and Customer Loyalty in Commercial Banks of Butwal Sub- Metropolitan City - Upadhyaya, Yasodha; Prasad Chaudhary, Bhagwati (Kalika Journal of Multidisciplinary Research, 2025)
The primary objective of this study is to examine the relationship between the key dimensions of Corporate Social Responsibility (CSR) namely, Customer Factor, Shareholders and Supervisory Board Factor, Employees Factor, and Society Factor and their influence on Customer Trust and Customer Loyalty in commercial banks. This study further aims to identify which CSRdimension has the most significant impact on building and sustaining trust and loyalty among bank customers. The study utilized an explanatory research design. Respondents were selected using the Cochran formula for an unknown population size, and data were collected via a structured questionnaire using convenience sampling. The responses were gathered from customers of various commercial banks. Analytical techniques such as descriptive statistics, correlation analysis, and multiple regression analysis were applied to identify relationships between CSR dimensions and customer trust and loyalty. The results revealed that Customer Factor and Society Factor are the most influential CSR dimensions affecting Customer Trust and Customer Loyalty in commercial banks. These findings suggest that socially responsive actions and customer-focused practices play a key role in shaping positive customer perceptions. Banks that prioritize their societal responsibilities and customer welfare are more likely to gain trust and loyalty. Strategic investment in these CSR areas is crucial for sustainable customer relationships.